Lithuanian bibliophiles in the XVIII century - Levas Vladimirovas (Knygotyra)
The level of culture, education, publishing, and book dissemination influences the number of bibliophiles in society. During the Age of Enlightenment, better conditions for the collection of books were created in Lithuania. However, the bibliophiles in Lithuania were mostly aristocrats. They created wonderful collections in their palaces. Later, most of those books enriched various state and research libraries.